Evidence-based production framework for herbal medicine regulation in Indonesia - Kashuri, Mohamad; Ikrar, Taruna; Sutriyo; Mun’im, Abdul; Yanuar, Arry (Frontiers in Pharmacology, 2026)
This narrative review synthesizes 2015–2025 evidence on evidence-based production (EBP) of herbal medicines with emphasis on advanced production technologies, omics-enabled authentication, quality by design (QbD), and regulatory harmonization relevant to Indonesia. We map how in vitro root culture, bioreactor scale-up, elicitation/metabolic engineering, and nanotechnology address supply variability and improve consistency; how DNA barcoding/metabarcoding and metabolomics with chemometrics underpin identity and chemical reproducibility; and how ASEAN/WHO initiatives enable ‘loose harmonization’ while preserving traditional diversity. We argue for a two-key batch-release specification (genomic × metabolite) and validated omics workflows within GLP to strengthen traceability, with real-world evidence and digital pharmacovigilance extending safety monitoring post-market. We translate these elements into an actionable framework for the Indonesian FDA (BPOM) to operationalize EBP through regulation, cross-sector training, and reliance pathways, positioning Indonesia as a regional hub for evidence-based herbal regulation.